Perspectives on managing man-environment relationship - Chakraborty, Satyesh C.; East-West Environment and Policy Institute; Southeast Asian Universities Agroecosystem Network; SUAN Information Support Service; Ford Foundation; East-West Center (1983)
This paper attempts to focus on the need for proper understanding of the relationship between man and environment in the context of environment management. Man-environment relationship has now become a paradox and this really is man's own creation. Landscape approach provides a better basis for understanding man-environment relationship. Therefore concepts of physical landscape, cultural landscape, ecology and ecosystem should become the integral part of the education for environment management.
Introduction -- Placement of man in nature -- Interdependence of education and management -- Meaning of environmentalism -- The meaning of habitat -- Meaning of ecology -- Basic tasks of environment management.
Photocopy.
This document has been provided by EAPI as part of its SUAN Information Support Service. The goal of this service is to make current literature relating to human ecology and agroecosystems research available to scientists participating in the Southeast Asian Universities Agroecosystem Network. Partial funding for this service is provided by a Ford Foundation grant to the East-West Center.
Keywords: Human-environment.; Human ecology; Environmental education; Cultural landscapes; Environmentalism